2011
DOI: 10.1128/mbio.00199-11
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of Cephalosporin Resistance in Enterococcus faecalis

Abstract: Antibiotic-resistant enterococci are major causes of hospital-acquired infections and therefore represent a serious public health problem. One well-known risk factor for the acquisition of hospital-acquired enterococcal infections is prior therapy with broad-spectrum cephalosporin antibiotics. Enterococci can proliferate in patients undergoing cephalosporin therapy due to intrinsic cephalosporin resistance, a characteristic of the genus Enterococcus. However, the molecular basis for cephalosporin resistance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 46 publications
5
85
1
1
Order By: Relevance
“…The D39 genome and other strains also harbor two more serine/threonine phosphatase homologs (SPD_0539 and SPD_1061, and equivalents in others), but they do not possess any sequence similarity and lack the conserved catalytic motifs, I to XI, the hallmarks of the eukaryote-like PP2C family of phosphatases (49). Thus, the successful creation of D39⌬phpP and 6A⌬phpP mutants displaying no growth defects, as has also been reported for STP mutants derived from S. aureus N315 (6), S. pyogenes M1SF370 M1T1 5448 (1), and Enterococcus faecalis (20), emphasizes the fact that PhpP is not essential for either pneumococcal growth or survival. From these published studies and the present study, we conclude that the successful creation of STP mutants in general is due to an appropriate vectorbased deletion strategy that allows nonpolar and markerless deletion.…”
Section: Discussionmentioning
confidence: 75%
“…The D39 genome and other strains also harbor two more serine/threonine phosphatase homologs (SPD_0539 and SPD_1061, and equivalents in others), but they do not possess any sequence similarity and lack the conserved catalytic motifs, I to XI, the hallmarks of the eukaryote-like PP2C family of phosphatases (49). Thus, the successful creation of D39⌬phpP and 6A⌬phpP mutants displaying no growth defects, as has also been reported for STP mutants derived from S. aureus N315 (6), S. pyogenes M1SF370 M1T1 5448 (1), and Enterococcus faecalis (20), emphasizes the fact that PhpP is not essential for either pneumococcal growth or survival. From these published studies and the present study, we conclude that the successful creation of STP mutants in general is due to an appropriate vectorbased deletion strategy that allows nonpolar and markerless deletion.…”
Section: Discussionmentioning
confidence: 75%
“…The E. faecalis kinase/phosphatase pair IreK/IreP is involved in intrinsic resistance against cephalosporin, as evidenced by the fact that mutants lacking ireK exhibit cephalosporin susceptibility, whereas mutants lacking ireP are hyperresistant (112). A subsequent study suggested that IreK/IreP regulates the phosphorylation state of the IreB protein, which would control a cephalosporin resistance pathway through an undetermined mechanism (113).…”
Section: One-component Systemsmentioning
confidence: 99%
“…One important well-characterized factor that is required for cephalosporin resistance is a specialized low-affinity PBP (Pbp5) that does not get inactivated by cephalosporins and can therefore perform cross-linking of peptidoglycan to permit growth in the presence of the antibiotic (6,7). Although required, Pbp5 is not sufficient for resistance, as mutations in other loci render E. faecalis susceptible to cephalosporin by mechanisms that have not been fully worked out (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%